ANALISIS PENGARUH PERMANENT DIFFERENCES, TEMPORARY DIFFERENCES, LPBTD, LNBTD DAN TINGKAT HUTANG TERHADAP PERSISTENSI LABA - Mirna Dyah Praptitorini S; Ita Nur Rahmawati (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2017)
This study aims to examine the factors that affect the persistence of earnings.Factors affecting earnings persistence consist of permanent differences, temporarydifferences, Large Positive Book Tax Differences (LPBTD), Large Negative Book TaxDifferences (LNBTD), and debt levels. The sampling method used is pruposive samplingwith the following criteria, 1. Manufacturing companies listed on the BEI and publishthe audited financial statements as of December 31 consistently and completely from2010-2013 and not delisted during the observation period of the study. 2 The financialstatements are denominated in rupiah. Due to the research conducted in Indonesia, thefinancial statements used are those which are stated in Rupiah. 3. The Company did notincur any losses in commercial financial statements and fiscal financial statements duringthe year of observation. The reason is that carryforward losses are a deduction of deferredtax expense and recognized as deferred tax assets so as to obscure the meaning of booktax differences (Hanlon, 2005). 4. The Company did not compensate tax due to lossduring the previous years.There are 146 companies that have been rated corporate governance index.Based on the criteria of this study obtained 71 companies used as sample research. Theanalysis technique used to analyze the hypothesis of this research is multiple linearregression analysis. The results of this study show that permanent differences have anegative and significant effect on profit persistence. Temporary differences have asignificant negative effect on earnings persistence. Large Positive Book-Tax Differences(LPBTD) has no significant effect on earnings persistence. Large Negative Book-TaxDifferences (LNBTD) have no significant effect on earnings persistence. The debt levelhas no significant effect on earnings persistence. This means that debt levels can notpredict earnings persistence.